1993
DOI: 10.1002/pen.760331909
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and experimental study of the die drawing of circular rods through conical dies

Abstract: An analysis is presented of the process of die drawing isotropic polymers, in the form of circular rods, to produce highly oriented materials with enhanced mechanical properties. The stresses in a small element of material undergoing the drawing process have been analyzed using a force‐equilibrium approach and the initial yield and flow stresses in the material have been predicted from the von‐Mises yield criterion. The stress‐strain‐strain rate characteristics of the polymer used in the analysis were deduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…In these previous experiments conical dies with a semiangle of 15° were used, with a parallel land at the exit equal in length to the die exit diameter. Recently, theoretical analysis of the die drawing of rods suggested that the polymer does not leave the die wall in the conical region 18–20. To verify this, dies were made without any land and drawing experiments were carried out using a video camera to monitor the product diameter at the die exit during the run.…”
Section: Resultsmentioning
confidence: 99%
“…In these previous experiments conical dies with a semiangle of 15° were used, with a parallel land at the exit equal in length to the die exit diameter. Recently, theoretical analysis of the die drawing of rods suggested that the polymer does not leave the die wall in the conical region 18–20. To verify this, dies were made without any land and drawing experiments were carried out using a video camera to monitor the product diameter at the die exit during the run.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the usual deviatoric criteria that have been adopted as a first approximation by many authors (e.g. [14,20]) for the die-drawing process should in general be replaced by a more realistic criterion taking into account explicitly the effect of the hydrostatic component of stress.…”
Section: Introductionmentioning
confidence: 99%
“…It indicates that an uneven force distribution existed inside the die during die drawing process. Indeed, such hypothesis had also been proposed by Ward et al by using a force equilibrium approach [32] and finite element simulation [33], respectively.…”
Section: Waxd Mapping Results Along Drawing Directionmentioning
confidence: 88%
“…It was also proven to be applicable for various material geometry, including but not limited to tubular products [20] and multi filaments [20]. Similar to extrusion and wire drawing in which a die was also employed [10,[27][28][29][30][31], a heterogeneous strain-stress distribution was found inside the die area for diedrawing process [32,33]. Ward et al [32] first analyzed the axial stress distribution as a function of the distance to the die entrance for die-drawing process by using a force-equilibrium approach as well as the von-Mises criterion.…”
Section: Introductionmentioning
confidence: 99%